BUSINESS STRATEGIES IN UNSTABLE INSTITUTIONAL ENVIRONMENT – CASE OF BRIC COUNTRIES - Rakita, Branko; Azdejković, Dragan; Marković, Dušan (Serbian Journal of Management, 2012)
The visionary idea of BRIC[1] countries and their leading position in the development of global economy, conceived by the leading investment bank Goldman Sachs more than a decade ago, came under heavy skepticism. However, what many doubted came true. At the end of 2011 BRIC countries generated approximately 26% of global GDP, and their share in the growth of global GDP was more than 50%. The impressive growth of BRIC countries has been in large measure due to FDI inflow[2]. Intensive FDI inflow and economic development have not been followed by improved institutional efficiency. This article will show that inefficient institutions in BRIC countries have not been discouraging to MNCs[3], who were predominantly led by the extent and the growth dynamics of the market. Modifications to business strategies applied in developed countries by MNCs, in order to manage unstable institutional environment in BRIC countries, will be analyzed. The conclusion is that the key modification is establishment of strong relationships with local stakeholders, in order for MNCs to gain necessary knowledge of the new business environment and create a sound basis for institutional efficiency improvement. Key words: BRIC countries, FDI, institutions, business strategy [1] Brazil, Russia, India and China [2] Foreign Direct Investments [3] Multinational Companies